Green SÖP extended: The socio-ecological panel surveys 2020 and 2022 - Manuel Frondel; Leonie Matejko; Daniel Osberghaus; Stephan Sommer; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
The proliferation of instruments targeted at combatting climate change necessitates evidence-based evaluation to identify strategies that are not only effective and cost-efficient, but also supported by the population. In Germany, the data needed to support such analysis is scarce, however. A rare exception is Green SÖP, a panel data set that was established within the project Eval-MAP funded by the German Ministry of Education and Research (BMBF). Green SÖP encompasses household data collected by the survey institute forsa over four years, spanning 2012 - 2015. The BMBF-funded project Eval-MAP 2 extends the Green SÖP panel data set by two additional surveys conducted in 2020 and 2022 and covering mitigation and adaptation behavior. – – Die Zunahme von Instrumenten zur Bekämpfung des Klimawandels erfordert eine evidenzbasierte Bewertung, um Strategien zu ermitteln, die nicht nur wirksam und kosteneffizient sind, sondern auch von der Bevölkerung unterstützt werden. In Deutschland sind die Daten, die für eine solche Analyse benötigt werden, jedoch spärlich. Eine seltene Ausnahme ist Green SÖP, ein Paneldatensatz, der im Rahmen des vom Bundesministerium für Bildung und Forschung (BMBF) geförderten Projekts Eval-MAP erstellt wurde. Green SÖP umfasst Haushaltsdaten, die vom Umfrageinstitut forsa über einen Zeitraum von vier Jahren (2012 - 2015) erhoben wurden. Das vom BMBF geförderte Projekt Eval-MAP 2 erweitert den Green SÖP-Panel-Datensatz um zwei zusätzliche Erhebungen in den Jahren 2020 und 2022, die das Vermeidungs- und Anpassungsverhalten abdecken.
Keywords: Q3; Q4; 330; Household panel; climate policy